ANALISIS PENGARUH PERSEPSI KONSUMEN PRIA DAN WANITA TERHADAP IKLAN TELEVISI PADA SIKAP DAN NIAT PEMBELIAN : STUDI PADA IKLAN PRODUK KOSMETIKA - , Rizka F. Sarastri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Advertising is a form of communication which is used to attract potential customers to purchase or consume the products and services of a brand. Marketers success in influencing consumer behavior is more dependent on how they understand about consumer behavior. Positive perceptions and attitudes toward advertising can lead to intentions to purchase or even purchase action. To that end, marketers must understand how consumers make purchase decisions. Advertising on television can influence consumer attitudes and perceptions of both the consumer and the brand advertising products advertised. Same perception and attitude toward the ad can appear differently depending on each consumer. Different attitudes and perceptions towards advertising arise because of differences in the reception and interpretation of television commercials on different gender, men and women. In this study measured the effect of consumer perceptions of men and women on television advertising of cosmetic products on the attitude and purchase intention cosmetics. The purpose of this study was to determine consumer perceptions of men and women on television advertising of cosmetic products, to determine the relationship between the perception of television advertising on consumer attitudes, as well as to determine the relationship between consumer attitudes and purchase intentions. This study is non-experimental research design using survey by providing a structured questionnaire to the participants to perform hypothesis testing. Sampling was done by rotating the study of television advertising of cosmetic products through a laptop. Once the ad is finished airing, participants were given a questionnaire to be filled with a clear and complete. Test results using a paired t-test is known that the female consumer attitudes toward television advertising of cosmetic products more positive attitude than male consumers. The test results by linear regression perseps stated that the influence of consumers on television advertising of cosmetic products on consumer attitudes men at 37.8% while 20.9% of the female consumer. Also note also that consumer attitudes toward television advertising of cosmetic products on the consumer's purchase intention influential men at 40.8% while in female consumer consumerâs attitudes toward television advertising has no influential in consumerâs purchase intention